Autophagy during Early Virus–Host Cell Interactions. Issue 12 (8th June 2018) - Viret, Christophe; Rozières, Aurore; Faure, Mathias
Abstract: Autophagy refers to the conserved, multi-step mechanism that delivers cytosolic cargoes to vesicles of the endo-lysosomal system for degradation. It maintains cellular homeostasis by ensuring the continuous degradation of misformed/senescent intracellular components and the associated recycling of nutrients. Autophagy also represents an important cell-intrinsic defense mechanism against invasion by intracellular pathogens, including viruses. Autophagy might oppose viral invasion by targeting viral particles or viral components for degradation. It can also promote the interaction of viral constituents with receptors specialized in the activation of innate immunity pathways or facilitate the activation of anti-viral adaptive immunity. In response to such pressures, viruses have evolved various sophisticated strategies to avoid anti-viral autophagic responses or to manipulate the autophagic machinery to promote their own replication. This review focuses on our current knowledge of autophagy-related events that take place at early stages during interaction of viruses with host cells as well as on their associated consequences in terms of virus replication and cell fate. Graphical abstract: Highlights: Autophagy can contribute to direct or indirect antiviral defense mechanisms. Virus sensing by invariant receptors can rapidly induce autophagy. Viruses can manipulate autophagy to interfere with inflammation and innate immunity. Viruses can utilize host components early in infection to escape autophagy. Autophagy factors can benefit to viruses through non-autophagic events.